The Salish Sea Boundary Straits: "Historic Internal Waters" or Territorial Seas?. (3rd April 2017) - Allen, Craig H.
ABSTRACT: The legal classification of the boundary straits of the Salish Sea between the western United States and Canada as either historic internal waters or territorial seas, subject to a right of innocent or transit passage, has been the subject of periodic debate within the U.S. government since the United States and Great Britain entered into the 1846 Oregon Treaty. As neither state has made an express public claim of historic title to the waters, any evidence for such a claim must be sought in less explicit and sometimes conflicting sources. This article applies the United States' legal test for a historic waters claim, recently set out in the U.S. Department of State's analysis of China's claims in the South China Sea, and concludes that the boundary waters of the Salish Sea would not meet that test. Accordingly, the waters of the Salish Sea boundary straits on the United States' side of the international boundary must be considered a territorial sea.